2013
DOI: 10.3329/fmcj.v8i1.16887
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pre-Existing Corneal Astigmatism in Age Related Cataract Patient

Abstract: :Cataract surgery is no more a blind rehabilitation surgery, it absolutely gives normal vision. In the era of modern cataract surgery patients expectations are also high about visual outcome. This prospective study was carried out to investigate the magnitude and pattern of pre-existing corneal astigmatism in age related cataract patient at . Astigmatism is in other direction is defined as oblique. On keratometry, when vertical reading (k1) was found greater than horizontal (k2) was considered WTR astigmatism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Identical results have been reported by other studies. 6,7,9,12 The lower range of keratometry values was higher as compared to other studies 40.25 to 50.00 D vs 38.00 to 49.00 D reported by Lekhanont et al 9 and 38.00 to 48.00 D by Ferrer-Blasco et al 4 The highest range was seen in the study reported by Guan et al 7 This study was limited by a small number of subjects. So, it may not represent the data of the whole population of Western Nepal.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Identical results have been reported by other studies. 6,7,9,12 The lower range of keratometry values was higher as compared to other studies 40.25 to 50.00 D vs 38.00 to 49.00 D reported by Lekhanont et al 9 and 38.00 to 48.00 D by Ferrer-Blasco et al 4 The highest range was seen in the study reported by Guan et al 7 This study was limited by a small number of subjects. So, it may not represent the data of the whole population of Western Nepal.…”
Section: Discussionmentioning
confidence: 54%
“…Studies in the Thai population (62.2%) and various studies in the Chinese population (58.2%, 53.2%, 50%) resembled our result. 6,7,8,9 Rashid et al 12 reported a much higher prevalence of ATR (79%). However, WTR astigmatism was more common among the Germans (46.8%).…”
Section: Discussionmentioning
confidence: 98%
“…Thirty five percent (35%) pre-operative patient had 1D or more corneal astigmatism and sixty five percent (65%) had less than 1D corneal astigmatism. MA Rashid et al 10 observed that the mean corneal astigmatism was 1.17±0.75 diopter. The percentage of preexisting corneal astigmatism was 1D or less was in 408 cases (69.6%), more than 1D and less than 1.5D in 302 cases (27.6%) and more than 1.5D and less than 2D in 20 cases (2.8%).…”
Section: Discussionmentioning
confidence: 99%